Activity in the Fronto-Parietal and Visual Cortex Is Modulated by Feature-Based Attentional Weighting - Lanssens, Armien; Mantini, Dante; de Beeck, Hans Op; Gillebert, Celine R. (Frontiers in Neuroscience, 2022)
In day-to-day dynamic activities where sensory input is abundant, stimulus representations in the visual cortex are modulated based on their attentional priority. Several studies have established the top-down role of a fronto-parietal dorsal attention network in selective attention. In the current study, we aimed to investigate whether activity of subregions of this network and the visual cortex is modulated by feature-based attentional weighting, and if so, whether their timecourses of activity are correlated. To this end, we analyzed fMRI data of 28 healthy subjects, who performed a feature-based go/no-go task. Participants had to attend to one or two colored streams of sinusoidal gratings and respond to each grating in the task-relevant stream(s) except to a single non-target grating. Univariate and multivariate fMRI results indicated that activity in bilateral fronto-parietal (frontal eye fields, intraparietal sulcus and superior parietal lobe) and visual (V1-V4, lateral occipital cortex and fusiform gyrus) regions was modulated by selecting one instead of attending to two gratings. Functional connectivity was not significantly different between fronto-parietal and visual regions when attending to one as opposed to two gratings. Our study demonstrates that activity in subregions of both the fronto-parietal and visual cortex is modified by feature-based attentional weighting.